Polskie kontyngenty wojskowe na wschodniej flance NATO a wzmocnienie systemu bezpieczeństwa w wymiarze lokalnym i regionalnym .......... 93 - Kozerawski, Dariusz (Bezpieczeństwo regionalne: Węzłowe problemy i procesy, 2020)
In the elaboration problems concerning Polish Military Contingents’ participation in the international NATO operations of their quantitative scale and the assignment range were introduced. Besides, the strategic threats were indicated in the aspect of the participation of Polish Armed Forces in NATO operations. First of all, the author concentrated on the approximation of the scale and the real meaning of the participation of Polish Military Contingents in NATO activities on its eastern flank in the aspect of the possibility of strengthening of the security system in this region. Additionally, the significant part of the author’s opinion was based on the field research in the zones of war-activities and areas of stabilization during the NATO operation on Balkans (Bosnia and Herzegovina, Kosovo), Afghanistan and Iraq.